Penggunaan Artificial Intelligence (AI) dan Implikasinya terhadap Kinerja di UPT Perpustakaan IAIN Curup: - - Herawati, Herawati; Buwono, Hamengku; Fakhruddin (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to identify the use of artificial intelligence (AI) and the implications of its use on the performance of staff and librarians at the Library of IAIN Curup, and the challenges and solutions in its use. This study uses a qualitative research approach with a case study as the research design. Research data were collected through interviews, observations, and analysis of related documents. The results of the study indicate that the use of AI at the Library of IAIN Curup has become part of the modernization effort in library management. AI is used not as a primary service, but as a tool that supports administrative tasks, promotions, and library collection management. The use of AI has a significant impact on the performance of staff and librarians. AI has helped speed up work processes, increase efficiency, and reduce the administrative burden. By utilizing AI, librarians can focus more on information services and more strategic collection management. The challenges in using AI include the absence of institutional policies in the implementation of AI, integration of AI with existing systems, the absence of formal training and continuous competency development and low interest in adopting new technologies.